Sistem Pendukung Keputusan Pengangkatan Pegawai Negeri Sipil Dalam Jabatan Pimpinan Tinggi Pratama Menggunakan Metode Simple Addictive Weighting (Saw) Pada Badan Kepegawaian Daerah Kabupaten Karo - Nina Karina Lolo Bintang (Cattleya Darmaya Fortuna, 2020)
The recruitment of the Primary High Leadership positions at BKD is carried out openly by forming a selection committee with full responsibility starting from the administrative process of the candidates, implementing the exam and determining the value obtained. Another finding is the accumulation of files because the administrative requirements require documents from the registering candidates. The SAW method is more efficient because the time required for calculation is shorter. The SAW method requires a decision matrix normalization process (X) to a scale that can be compared with all existing alternative ratings. Of the four people who took part in the selection, the first rank was Canika Sinulingga with a score of 18.